PERAN BUMDES DALAM PEMBERDAYAAN MASYARAKAT DESA COKROKEMBANG KECAMATAN NGADIROJO KABUPATEN PACITAN - Rahmadanik, Dida (Universitas 17 Agustus 1945 Surabaya, 2018)
Role of bumdes in empowerment of district community in Ngadirojo Pacitan. People in Cokrokembang Village have many businesses, both in the field of brick making, batik making, broom making, screen printing, cake maker. But until now their business is still managed independently. In this study researchers used qualitative methods with descriptive approach that is by doing observations and interviews directly with business actors and with the Village Cokrokembang. Until now that has been running only for units of savings and loans. Bumdes has not been instrumental in improving the promotion and marketing of products from the Cokrokembang community. If Bumdes in Cokrokembang village is well managed then it is expected to increase community empowerment in terms of economy.Â Keywords: village owned enterprise, independent village, empowerment.